The interplay and synergistic relationship between urban land expansion and urban resilience across the three principal metropolitan regions of the Yangtze River Basin - Lei Ning; Shuangqing Sheng; Yue Meng (Scientific Reports)
Abstract As global urbanization advances, the expansion of urban land has subjected cities to increasingly frequent and extensive external disturbances, often revealing limitations in disaster prevention and mitigation capacities, particularly in regions characterized by high urbanization, environmental degradation, and recurrent natural disasters. This study investigates the association between urban land expansion and urban resilience, developing a targeted analytical framework to assess their coupling and coordination. Leveraging remote sensing data on land use and socio-economic development indicators, we constructed a comprehensive evaluation index encompassing social, economic, ecological, and infrastructural dimensions. Examining three principal urban agglomerations in China’s Yangtze River Basin, we analyzed the spatial-temporal dynamics and rates of change in urban land area and resilience levels from 2000 to 2020. A coupling coordination model was applied to assess the alignment between the rate of urban land expansion and resilience improvement, ultimately aiming to derive actionable policy recommendations. The results demonstrate that: (1) both the intensity and rate of urban land expansion across urban agglomerations in the Yangtze River Basin have declined, indicating a shift in urbanization focus from “land expansion” to “quality enhancement,” with a slowdown in the conversion of agricultural to urban land. (2) Urban land expansion exhibits weak directionality, with land expansion occurring uniformly within the region. (3) On the whole, resilience levels in the Yangtze River Basin’s urban agglomerations remain moderate or lower, although showing gradual improvement. (4) The coordination between urban land area and urban resilience across the basin is limited, with a declining alignment between urban land expansion and resilience enhancement rates, signaling an emerging imbalance. By assessing the coordination between urban land expansion and resilience, this study seeks to inform policy development on urban land management and resilience enhancement within the Yangtze River Basin’s urban agglomerations.